Corporate Social Responsibility (CSR) Accounting Treatments on Financial Performance: Case Study in Manufacturing Public Companies - Marota, Rochman; Suryadnyana, Nyoman Adhi; Sjam, Juska Meidy Enyke; Supriadi, Taufiq (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
The primary aim of this research is to evaluate the impact of Corporate Social Responsibility (CSR) on the financial performance of organizations. The evaluation of the financial performance of the company is carried out by employing key indicators such as Return on Equity (ROE), Return on Assets (ROA), and Return on Sales (ROS). In the current study, Corporate Social Responsibility (CSR) is considered an exogenous variable, whereas Return on Equity (ROE), Return on Assets (ROA), and Return on Sales (ROS) are viewed as endogenous factors. The study's sample consisted of manufacturing enterprises publicly listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. The material was acquired through documentary research methods and an extensive examination of pertinent literature. The researchers utilized a purposive sampling methodology to choose the sample for the study, wherein each period encompassed a total of 41 organizations. The data underwent multivariate regression analysis for analysis. The study's results suggest that there is a statistically significant and positive relationship between corporate social responsibility (CSR) and a company's financial success, as measured by return on equity (ROE) and return on assets (ROA). Nevertheless, it is important to acknowledge that Corporate Social Responsibility (CSR) has a detrimental impact on the company's Return on Sales (ROS).